Growth differentiation factor 11 delivered by dairy Lactococcus lactis strains modulates inflammation and prevents mucosal damage in a mice model of intestinal mucositis - Américo, Monique Ferrary; Freitas, Andria dos Santos; da Silva, Tales Fernando; de Jesus, Luís Cláudio Lima; Barroso, Fernanda Alvarenga Lima; Campos, Gabriela Munis; Santos, Rhayane Cristina Viegas; Gomes, Gabriel Camargos; Assis, Rafael; Ferreira, Ênio; Mancha-Agresti, Pamela; Laguna, Juliana Guimarães; et al. (Frontiers in Microbiology, 2023)
Mucositis is an inflammation of the gastrointestinal mucosa that debilitate the quality of life of patients undergoing chemotherapy treatments. In this context, antineoplastic drugs, such as 5-fluorouracil, provokes ulcerations in the intestinal mucosa that lead to the secretion of pro-inflammatory cytokines by activating the NF-κB pathway. Alternative approaches to treat the disease using probiotic strains show promising results, and thereafter, treatments that target the site of inflammation could be further explored. Recently, studies reported that the protein GDF11 has an anti-inflammatory role in several diseases, including in vitro and in vivo results in different experimental models. Hence, this study evaluated the anti-inflammatory effect of GDF11 delivered by Lactococcus lactis strains NCDO2118 and MG1363 in a model of intestinal mucositis induced by 5-FU. Our results showed that mice treated with the recombinant lactococci strains presented improved histopathological scores of intestinal damage with a reduction of goblet cell degeneration. It also observed a significant reduction of neutrophil infiltration in the tissue and immunomodulation of inflammatory markers Nfkb1, Nlrp3, Tnf, and Il10 in mRNA expression levels. Therefore, this study suggests that the use of recombinant L. lactis (pExu:gdf11) could offer a potential gene therapy for intestinal mucositis induced by 5-FU.